How empowering leadership influences medical workers' work–family conflict in the post-pandemic era: A moderated mediation model of leadership “black box” - Zhou, Haiming; Song, Xinping; Fang, Laitan; Shi, Kan; Liu, Ronghui (Frontiers in Psychology, 2022)
After experiencing the cruel COVID-19 pandemic, the status and mechanisms of leadership facing challenges related to the medical workers’ family-work conflict are of great concern. In the post-pandemic era, based on the role theory and stressor-detachment model, this study sought to break the ‘black box’ of negative effects rarely touched by leadership, research the mechanism and boundary conditions of negative effects, and explore the factors to reduce the negative effects. We recruited 1,010 Chinese medical workers fighting the COVID-19 on the frontline. The results revealed that there is a significant negative correlation between empowering leadership and work-family conflict, and this relationship was partially mediated by role stress, while psychological detachment moderated the relationship between role stress and work-family conflict, moreover, the psychological detachment moderated the mediating effect of empowering leadership on work-family conflict through role stress. Thus, a higher level of psychological detachment was less conducive to the medical workers’ family-work conflict. This study revealed the "black box" of the negative effects of leadership, which enriches and expands the theoretical value and practical significance for better playing the positive role of leadership, reducing the negative effects, and intervening in the work-family conflict of employees in the post-pandemic era.